Movement Patterns of Resident and Relocated Northern Bobwhites in East Texas - Xiangwen Liu; Montague Whiting Jr.; D. Scott Parsons; Donald R. Dietz (National Quail Symposium Proceedings, 2017)
We compared home range sizes and movement patterns of resident and relocated northern bobwhites (Colinus virginianus) on an area managed specifically for the species in the Pineywoods of east Texas. During the winters of 1990–1992, 155 south Texas, 136 east Texas, and 139 resident bobwhites were radiomarked, released, and thereafter regularly located. Bird locations were plotted on a digitized map, and home range sizes and movement patterns of each group of birds were estimated. Resident bobwhites moved longer daily distances in March and had larger home ranges during the nesting season (May-Jul) than relocated birds (P <= 0.05). Conversely, no differences were detected among groups in mean of daily distances moved in April or dispersal during the breeding season (Mar-Jun) (P 0.05). Annual dispersal distances (x¯ = 1.43 km) of birds that survived into November were similar among groups (P > 0.05). Managers that elect to relocate northern bobwhites should consider doing so in the fall and only into habitats of ample size.
Keywords: Colinus virginianus; movement patterns; northern bobwhite; relocation; Texas; transplant